2008
DOI: 10.1128/jvi.00185-08
|View full text |Cite
|
Sign up to set email alerts
|

Asparagine 631 Variants of the Chicken Mx Protein Do Not Inhibit Influenza Virus Replication in Primary Chicken Embryo Fibroblasts or In Vitro Surrogate Assays

Abstract: Whether chicken Mx inhibits influenza virus replication is an important

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
54
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 45 publications
5
54
2
Order By: Relevance
“…Neither of these proteins was able to reduce FLUAV replication in our hands, confirming earlier observations from other experimental setups by us and others (5,7). In contrast, the expression of mouse Mx1 and human MxA resulted in a strong protective effect against lowly and highly pathogenic FLUAV from both human and avian origin.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Neither of these proteins was able to reduce FLUAV replication in our hands, confirming earlier observations from other experimental setups by us and others (5,7). In contrast, the expression of mouse Mx1 and human MxA resulted in a strong protective effect against lowly and highly pathogenic FLUAV from both human and avian origin.…”
Section: Discussionsupporting
confidence: 80%
“…Later, Ko and coworkers reported that a singlenucleotide polymorphism at amino acid 631 is crucial for virus protection by chicken Mx (20). More recent reports from several laboratories are conflicting, some assigning and some not assigning antiviral activity to the chicken Mx protein (5,6,9,19,20,39,43). Thus, the question of whether Mx contributes to influenza virus resistance in the chicken has remained unanswered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, no association was found between the Mx genotype for the G/A polymorphism affecting amino acid position 631 and the survival of chicken experimentally infected in vivo with a highly pathogenic H7N1 avian influenza virus (Sironi et al, 2008). Similar results were obtained by Benfield et al (2008) in their study showing that the Asn631 allele of chicken Mx is unable to inhibit in vitro replication of 5 influenza strains.…”
Section: Introductionsupporting
confidence: 76%
“…Mx genes are also present in avian species, and some antiviral activity for chicken Mx linked to a serine-to-asparagine polymorphism at position 631 has been described (15). However, recent studies could not detect any antiviral effect of chicken Mx proteins against different strains of influenza A viruses (3,27). In any case, it is conceivable that newly emerging influenza A viruses acquire adaptive mutations in the mammalian host which allow them to escape Mx restriction.…”
Section: Discussionmentioning
confidence: 97%